2018
DOI: 10.3168/jds.2018-14671
|View full text |Cite
|
Sign up to set email alerts
|

Milk yield relative to supplement intake and rumination time differs by health status for fresh cows milked with automated systems

Abstract: Automated milking systems (AMS) provide the capability of adjusting the amount of supplemental concentrate offered to cows based on parity, days in milk, and milk yield; in many situations, more supplement is provided to those cows with higher production demands. To determine associations of subclinical ketosis (SCK) and blood β-hydroxybutyrate (BHB) with milk yield, supplement consumed in the AMS, rumination time, and the ratios of milk yield to supplement intake and milk yield to rumination time, we monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This study demonstrated that AMS herds have a prevalence of high rates of betahydroxybutyrate than those in conventional milking systems (Tatone et al, 2017). As for King et al (2018), cows producing more milk have more betahydroxybutyrate circulating in the blood, as well as a higher probability of having subclinical ketosis. According to these authors, cows that produce less are more able to obtain from the diet the energy they need.…”
Section: Increase In Subclinical Ketosismentioning
confidence: 73%
See 2 more Smart Citations
“…This study demonstrated that AMS herds have a prevalence of high rates of betahydroxybutyrate than those in conventional milking systems (Tatone et al, 2017). As for King et al (2018), cows producing more milk have more betahydroxybutyrate circulating in the blood, as well as a higher probability of having subclinical ketosis. According to these authors, cows that produce less are more able to obtain from the diet the energy they need.…”
Section: Increase In Subclinical Ketosismentioning
confidence: 73%
“…According to Tatone, Duffield, Leblanc, De Vries and Gordon (2017) and King, Sparkman, Leblanc and De Vries (2018), subclinical ketosis rates tend to increase in dairy herds under AMS. The reason is related to the increase in the number of milking events and milk production inherent to the AMS, especially at the beginning of lactation.…”
Section: Increase In Subclinical Ketosismentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Tatone et al (2017) reported that multiparous cows in AMS herds were more likely to have SCK than multiparous cows in conventional herds. Furthermore, researchers have reported that development of SCK in commercial AMS-milked cows was associated with greater production of milk relative to the amount of feed provided in the AMS during the first week postcalving (King et al, 2018), suggesting that inadequate supplementation at that time may be a contributing factor to the observed SCK.…”
Section: Introductionmentioning
confidence: 99%
“…Sugar supplementation supports microbial growth, particularly for fiber-digesting bacteria, speeding up fiber degradation and allowing for greater intake (de Ondarza et al, 2017); this in turn may help improve energy balance. Despite the worldwide exponential increase in AMS, to our knowledge, no previous studies have been conducted to investigate the effects of supplementing sugar to early-lactation cows in AMS, where energy demands may be greater compared with conventional milking herds (Tatone et al, 2017;King et al, 2018).…”
Section: Introductionmentioning
confidence: 99%